2016
DOI: 10.1002/chem.201604574
|View full text |Cite
|
Sign up to set email alerts
|

Does the S−H Bond Always Break after Adsorption of an Alkylthiol on Au(111)?

Abstract: The reaction mechanism for the formation of alkyl thiol self-assembled monolayers (SAM) on Au(111) is still not clearly understood. Especially, the role of defects on the chemisorption process is an important goal to be addressed. In this work, different minimum energy reaction paths for R-SH dissociation of thiols (with long and short chains and dithiol species) adsorbed on gold adatom are calculated by using periodic density functional theory (DFT). Our results show a lower energy barrier for the RS-H bond d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…This point was also very concluded in our recent investigation on the thiol SAM formation reaction paths analysis. [36] The surface is indeed found to be affected by adsorption of the thiol radicals. No barrierless adatom formation was observed, however Au-atoms were pulled out of the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point was also very concluded in our recent investigation on the thiol SAM formation reaction paths analysis. [36] The surface is indeed found to be affected by adsorption of the thiol radicals. No barrierless adatom formation was observed, however Au-atoms were pulled out of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34] It should be noted that the adsorption of thiol molecules cannot be generalized to one model, since the polarization of the sulphur atom is very sensible to the thiol chain; at least this is what we would like to show in results presented here. This means that the adsorption process involving S-H bond breaking [35][36][37][38] and or adatom adsorption [39][40][41][42] is expected to be dependent of the type of thiol.…”
Section: Introductionmentioning
confidence: 99%
“…This value is further used as a reference value in order to quantify the stabilization of the SAM mixture. 30,54,55 ΔE ads is the lowest for all segregated mixtures whatever the S-CC/S-CH 3 molar ratio ( Figure 6). It shows that intermolecular interactions are thermodynamically favored in segregated mixtures.…”
Section: ■ Computational Resultsmentioning
confidence: 93%
“…[1,2] It has also been shown that thiol mobility is reduced as van der Waals interactions among adsorbed molecules increase, which resultsi nadecrease of the size of the ordered domains, af act observed for alkanethiols as af unction of the hydrocarbon chain length. It is well-known that the adsorptionp rocess results in the formationo fo rdered molecular domains, the size of which depends on the temperature, thus reflecting the surface mobilityo fa dsorbed thiol species on the Au(111)s urface.…”
Section: Introductionmentioning
confidence: 97%